Efficacy and safety of mycophenolate mofetil for steroid reduction in neuromyelitis optica spectrum disorder: a prospective cohort study - Akatani, Ritsu; Chihara, Norio; Koto, Shusuke; Mori, Sotaro; Kurimoto, Takuji; Nakamura, Makoto; Tachibana, Hisatsugu; Otsuka, Yoshihisa; Ueda, Takehiro; Omori, Takashi; Sekiguchi, Kenji; Matsumoto, Riki (Immunological medicine, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is a rare autoimmune inflammatory disease that can affect multiple generations and cause complications with long-term prednisolone treatment. This study aimed to evaluate the efficacy and safety of mycophenolate mofetil (MMF) in preventing NMOSD relapse while reducing prednisolone dosage. The trial involved nine patients with NMOSD who received MMF along with prednisolone dose reduction. MMF was effective in achieving prednisolone dose reduction without relapse in 77.8% of patients, with a significant decrease in mean annualized relapse rate. All adverse events were mild. The findings suggest that MMF could be a viable treatment option for middle-aged and older patients who require steroid reduction. jRCT, jRCTs051180080. Registered February 27th, 2019-retrospectively registered, https://jrct.niph.go.jp/en-latest-detail/jRCTs051180080.